Odpowiedzi

2010-04-07T18:47:23+02:00
Hey:)

a) 1/2x-3/4[x-(4x+1)]=1-x+1/4
1/2x-3/4(x-4x-1)=1-x+1/4
1/2x-3/4x+3x+3/4x=1-x+1/4
1/2-3/4x+3x+x=1+1/4-3/4
2/4x-3/4x+3x+x=2/4
4i2/4x-3/4x=2/4
18/4x-3/4x=2/4
15/4x=2/4 / * 4/15
x=8/60
x=2/15
b)2/3(3x-1)-2/3[2x+3(x-2)]=1
2x-2/3-2/3(2x+3x-6)=1
2x-2/3-4/3x-2x+4=1
2x-4/3x-2x=1-4+2/3
-4/3 x=1i2/3 - 4
-4/3 x=-2i1/3 /* (- 3/4)
x= (- 7/3) * (-3/4)
x=1i3/4
2010-04-07T18:53:11+02:00
A)1/2x - 3/4[x-(4x + 1)]=1 - x + 1/4 |x4
2x - 3[x-(4x + 1)]=4 - 4x + 1 |-1
2x -12x=3 - 4x
-10x=3 - 4x |+4x
-6x=3 |:(-6)
x=-1/2

B)2/3(3x - 1) - 2/3[2x + 3(x - 2)]=1 |x3
2(3x - 1) - 2[2x + 3(x - 2)]=3 |+2
6x - 2 - 10x=5
-4x - 2=5 |+2
-4x=7 |:(-4)
x=-1,75

Mam nadzieję ,że dobrze :)
Najlepsza Odpowiedź!
2010-04-07T18:54:51+02:00
A)
1/2x - 3/4 [x-(4x+1)]=1-x+1/4
½x-¾[x-4x-1]=1-x+¼
½x-¾x+3+¾=1-x+¼
½x-¾x+x=1+¼-3-¾
¾x=-2,5
x=-3⅓


B)
2/3(3x-1)-2/3[2x+3(x-2)]=1
2x-⅔-⅔[2x+3x-6]=1
2x-⅔-1⅓x-2x+4=1
2x-1⅓x-2x=1+⅔-4
-1⅓x=-2⅓
x=1¾
1 5 1